Proceedings of the 15th LACCEI International Multi-Conference for Engineering, Education, and Technology: “Global Partnership F 2017
DOI: 10.18687/laccei2017.1.1.435
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Security Reference Architecture for Cyber- Physical Systems

Abstract: Cyber Physical Systems (CPS) are physical entities whose operations are monitored, coordinated, controlled and integrated by a computing and communication core. Security for these systems requires solutions that are robust to threats, especially when securing critical infrastructures. Secure systems need to be built in a systematic way, where security and safety are not just add-ons or built in a piecemeal fashion but are able to handle their complexity in a safe and secure holistic way. All lifecycle stages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Romero and Fernandez [4] define a new model to represent CPS threads through architectural patterns and to consider their cross-domain effects. In particular, they propose an idea where there exists similar threads in different types of CPS which might be controlled in similar ways.…”
Section: Related Workmentioning
confidence: 99%
“…Romero and Fernandez [4] define a new model to represent CPS threads through architectural patterns and to consider their cross-domain effects. In particular, they propose an idea where there exists similar threads in different types of CPS which might be controlled in similar ways.…”
Section: Related Workmentioning
confidence: 99%
“…Our objective is not to define an RA for any type of CPS, but we will consider a specific type of system, a transportation system, specifically a maritime container cargo port. As we discuss in Section 7, an analysis of the relevant literature found that there are not many reference architectures for cargo ports ( [9] and Section 7). We show here a cargo port RA built of patterns described using UML models.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of the components and concepts defined in the SRA can better support our process, while at the same time, we address the problem of the typical complexity of this type of systems. SRAs have become useful tools that allow a better understanding of complex systems [17], such as cyber-physical systems [18]. In this way, our SRA is designed to allow the use of patterns of different kinds to ease the implementation of the system and improve the addition of non-functional requirements [19].…”
Section: Introductionmentioning
confidence: 99%